ANALISIS PENGARUH PERTUMBUHAN PENDUDUK, TINGKAT PENDIDIKAN DAN TINGKAT PARTISIPASI ANGKATAN KERJA (TPAK) TERHADAP KEMISKINAN DI PROVINSI PAPUA - Fransiska Vistalia Alo; I Wayan Sukadana (E-Jurnal Ekonomi Pembangunan, 2023)
The problem of poverty has a very urgent nature and has no clear boundaries. This is due not only to its continued upward trend, but also to its impact that transcends the economic sphere, encompasses social aspects and even threatens political stability within the country. Most countries with large populations also tend to have higher poverty rates compared to countries with smaller populations. Likewise, with the level of education and TPAK where inmany communities with low economies, opportunities to get adequate education, ranging from elementary to higher, are often limited, furthermore, if TPAK increases this can have a positive impact on economic growth. This study uses time series data with variables of population growth, education level, , TPAK, and poverty rate in the last 26 years, namely 1996-2021 until the number of observations is 26 observation points. Based on the results of data processing and testing simultaneously shows that population growth, education rate, and labor force participation rate (TPAK) affect simultaneously in Papua Province. Population growth has a negative and significant effect on poverty. The level of education, that is, the average length of schooling, has a negative and insignificant effect on poverty. The labor force participation rate (TPAK) has a negative and significant effect on poverty. keyword: Population Growth, Education Level, TPAK, Poverty